2020
DOI: 10.1136/bmjgh-2020-003325
|View full text |Cite
|
Sign up to set email alerts
|

Fighting non-communicable diseases in East Africa: assessing progress and identifying the next steps

Abstract: Sub-Saharan Africa has seen a rapid increase in non-communicable disease (NCD) burden over the last decades. The East African Community (EAC) comprises Burundi, Rwanda, Kenya, Tanzania, South Sudan and Uganda, with a population of 177 million. In those countries, 40% of deaths in 2015 were attributable to NCDs. We review the status of the NCD response in the countries of the EAC based on the available monitoring tools, the WHO NCD progress monitors in 2017 and 2020 and the East African NCD Alliance benchmark s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…7 Therefore, healthcare systems strengthening, increased investments and efficient use of resources are needed to counter the double burden of communicable and NCDs in SSA. 8 The established vertical healthcare structures in many countries, in particular those for HIV-care, risk contributing to inefficient use of resources and increased HIV-related stigma. 9 10 Thus, integration of the existing communicable and non-communicable healthcare infrastructure has become a recent policy and research focus to improve care for people living with NCDs (PLWNCDs) and PLWH alike.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Therefore, healthcare systems strengthening, increased investments and efficient use of resources are needed to counter the double burden of communicable and NCDs in SSA. 8 The established vertical healthcare structures in many countries, in particular those for HIV-care, risk contributing to inefficient use of resources and increased HIV-related stigma. 9 10 Thus, integration of the existing communicable and non-communicable healthcare infrastructure has become a recent policy and research focus to improve care for people living with NCDs (PLWNCDs) and PLWH alike.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 7 Therefore, healthcare systems strengthening, increased investments and efficient use of resources are needed to counter the double burden of communicable and NCDs in SSA. 8 The established vertical healthcare structures in many countries, in particular those for HIV-care, risk contributing to inefficient use of resources and increased HIV-related stigma. 9 10 …”
Section: Introductionmentioning
confidence: 99%
“…There has been an increased morbidity and mortality rate in Africa due to COVID-19, especially among individuals with comorbidities [14]. In addition, many African countries are burdened by NCDs such as diabetes mellitus, hypertension, heart failure, cancer, and asthma among others [15]. Studies have also shown that most people who succumb to COVID-19 suffer from one or more NCDs [16] [17].…”
Section: Background Informationmentioning
confidence: 99%
“…The upsurge of these NCDs threatens to further stretch the already fragile healthcare systems across the African continent [115] [116]. Previous analysis has projected that the morbidity and mortality due to NCDs such as diabetes and hypertension will likely supersede the scourge inflicted by infectious diseases by 2030 [15]. A major complication with NCDs is that they often co-exist with other diseases [116].…”
Section: Burden Of Communicable and Non-communicable Diseases In Africamentioning
confidence: 99%
“…According to global burden of disease study in 2017, Sub-Saharan Africa has seen a rapid increase of NCDs burden from 19% to 30% of the total diseases burden, between 1990 and 2017[2]. In a recent review of NCDs in the East Africa Community which includes Burundi, it was reported that cardiovascular diseases caused 13% of all NCDs related deaths, followed by malignant neoplasms (5.9%), respiratory diseases (2.1%), and diabetes mellitus (1.9%) according to data reported between 2000-2016[3].…”
Section: Introductionmentioning
confidence: 99%